NK cell immunophenotypic and genotypic analysis of infants with severe respiratory syncytial virus infection. (July 2015) - Noyola, Daniel E.; Juárez‐Vega, Guillermo; Monjarás‐Ávila, César; Escalante‐Padrón, Francisco; Rangel‐Ramírez, Verónica; Cadena‐Mota, Sandra; Monsiváis‐Urenda, Adriana; García‐Sepúlveda, Christian A.; González‐Amaro, Roberto
ABSTRACT Respiratory syncytial virus (RSV) is the leading cause of severe lower respiratory tract infection in infants. Reduced numbers of NK cells have been reported in infants with severe RSV infection; however, the precise role of NK cells during acute RSV infection is unclear. In this study the NK and T cell phenotypes, LILRB1 gene polymorphisms and KIR genotypes of infants hospitalized with RSV infection were analyzed. Compared to controls, infants with acute RSV infection showed a higher proportion of LILRB1+ T cells; in addition, a subgroup of infants with RSV infection showed an increase in LILRB1+ NK cells. No differences in NKG2C, NKG2A, or CD161 expression between RSV infected infants and controls were observed. LILRB1 genotype distribution of the rs3760860 A>G, and rs3760861 A>G single nucleotide polymorphisms differed between infants with RSV infection and healthy donors, whereas no differences in any of the KIR genes were observed. Our results suggest that LILRB1 participates in the pathogenesis of RSV infection. Further studies are needed to define the role of LILRB1+ NK in response to RSV and to confirm an association between LILRB1 polymorphisms and the risk of severe RSV infection.